2017
DOI: 10.4049/jimmunol.1600600
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fibroblasts Selectively Suppress Th1 Cell Responses through IDO1-Mediated Tryptophan Catabolism

Abstract: The development of rheumatoid arthritis (RA) is linked to functional changes in synovial fibroblasts (SF) and local infiltration of T lymphocytes. Fibroblasts possess the capacity to suppress T cell responses, although the molecular mechanisms of this suppression remain incompletely understood. In this study, we aimed to define the mechanisms by which noninflammatory SF modulate Th cell responses and to determine the immunosuppressive efficacy of RASF. Hence, the influence of SF from osteoarthritis or RA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“… 49 50 A recent study could show that the inhibition of T cell proliferation is at least partly mediated via depletion of tryptophan by synovial fibroblasts. 50 This study also showed that OA synovial fibroblasts are more efficient in suppressing T cell proliferation than RA synovial fibroblasts.…”
Section: Interactions Of Synovial Fibroblasts With T Cellsmentioning
confidence: 52%
“… 49 50 A recent study could show that the inhibition of T cell proliferation is at least partly mediated via depletion of tryptophan by synovial fibroblasts. 50 This study also showed that OA synovial fibroblasts are more efficient in suppressing T cell proliferation than RA synovial fibroblasts.…”
Section: Interactions Of Synovial Fibroblasts With T Cellsmentioning
confidence: 52%
“…In this regard, it is notable that Kyn is a ligand for the aryl hydrocarbon receptor that promotes Treg generation (for a review see [157]). Trp depletion also attenuates Th1 proliferation but does not affect Th2 or Th17 subsets, highlighting metabolic differences between these subsets [158] (Fig. 2).…”
Section: Kynurenine Lactatementioning
confidence: 90%
“…Finally, stromal cells contribute directly to immune response resolution and tissue repair, the latter being one of their best studied functions. Examples of “pro-resolution” factors produced by stromal cells include NOS2 (nitric oxide synthase 2) and NO (nitric oxide), which are released by lymph node FRC to constrain T cell proliferation (1012), and IDO1 (indoleamine 2,3-dioxygenase 1) produced by peripheral stromal cells, which similarly limits T cell proliferation by depleting the critical T cell metabolite tryptophan (13, 14). Thus, stromal cells in different tissues collectively regulate the strength, quality, and duration of immune responses via diverse and complementary mechanisms.…”
Section: The Diverse Roles Of Stromal Cells In Immunity and Inflammationmentioning
confidence: 99%